Influence of a Sustained Release Deslorelin Acetate Implant on Reproductive Physiology and Associated Traits in Laying Hens - Eusemann, Beryl Katharina; Sharifi, Ahmad Reza; Patt, Antonia; Reinhard, Ann-Kathrin; Schrader, Lars; Thöne-Reineke, Christa; Petow, Stefanie (Frontiers in Physiology, 2018)
The aim of this study was to develop an animal model with non-laying hens which would allow for investigation of the relationship between egg production and common diseases in hens. A total of 40 Lohmann Selected Leghorn hens were kept for 20 weeks in a floor housing system in two groups: group “Adult” (21 weeks of age) and group “Juvenile” (14 weeks of age). In each group, 10 hens were administered a 4.7 mg sustained release deslorelin acetate implant subcutaneously; in group “Adult” after, in group “Juvenile” before the onset of lay. In both groups, the remaining hens served as control hens. An examination of each hen was performed weekly, including ultrasonography to check for ovarian follicles, analysis of estradiol-17ß plasma concentration, and assessment of comb size. Digital radiographs of the keel bone were taken in experimental weeks 7 and 15. No follicles were detected on the ovary of treated hens for a certain time period which varied between individuals (between 8 weeks and until the end of the experiment). Estradiol-17ß concentrations were significantly higher in control hens. The comb was significantly smaller in treated hens. A lower prevalence of keel bone damage (group “Adult”) and foot pad dermatitis (both groups) was found in treated compared to control hens. These results show that a model with laying and non-laying hens can be achieved by administering a deslorelin acetate implant. Furthermore, they indicate a relationship between egg production and keel bone damage as well as foot pad dermatitis.